2006
DOI: 10.1017/s0012162206000041
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of adductor spasticity with BTX‐A in children with CP: a randomized, double‐blind, placebo‐controlled study

Abstract: Adductor spasticity in children with cerebral palsy (CP) impairs motor function and development. In a placebo‐controlled, double‐blind, randomized multicentre study, we evaluated the effects of botulinum toxin A(BTX‐A) in 61 children (37 males, 24 females; mean age 6 years 1 month [SD 3y 1mo]) with CP (leg‐dominated tetraparesis, n=39; tetraparesis, n=22; GMFCS level I, n=3; II, n=6; III, n=17; IV, n=29; V, n=6). Four weeks after treatment, a significant superiority of BTX‐A was observed in the primary outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
58
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 8 publications
0
58
0
5
Order By: Relevance
“…18 In these studies, a total of 284 children were assessed with 859 GAS scales of varying quality, using a variety of scale development techniques in the different study designs. Five recent studies 3,18,19,20,23 evaluated BTX-A treatment. These studies found significant and clinically relevant effects of treatment with BTX-A as measured by GAS.…”
Section: Goal Attainment Scaling Used In Effect Studies In Paediatricmentioning
confidence: 99%
See 4 more Smart Citations
“…18 In these studies, a total of 284 children were assessed with 859 GAS scales of varying quality, using a variety of scale development techniques in the different study designs. Five recent studies 3,18,19,20,23 evaluated BTX-A treatment. These studies found significant and clinically relevant effects of treatment with BTX-A as measured by GAS.…”
Section: Goal Attainment Scaling Used In Effect Studies In Paediatricmentioning
confidence: 99%
“…Most of the goals set in the six studies were in the areas of activities and participation, but body function goals, such as gait pattern 19,23 and range of motion, 18 were also assessed. The results of these studies show that GAS is sensitive to change when used to measure an effect of BTX-A and an effect of functional training in children.…”
Section: Goal Attainment Scaling Used In Effect Studies In Paediatricmentioning
confidence: 99%
See 3 more Smart Citations